Microbiological Quality of Vegetable and Juice Beverages in Sealed Containers in Samut Prakarn Province - Rangsipanuratn, Watcharin; Paungmoung, Porntip; Chuwongwattana, Sumonrat; Phumeesat, Potjaman; Nimmanee, Panjaphorn; Janwithayanuchit, Isaya (Journal of Health Science of Thailand, 2018)
The objective of this study was to analyze the microbiological quality of vegetable and juice beverages packaged in sealed containers collected from markets, grocery stores and department stores in all districts of Samut Prakarn province from March to May 2008. One-hundred and ninetyseven beverage samples were collected. The samples were analyzed for (i) coliform bacteria reported in term of most probable number (MPN), (ii) Escherichia coli, (iii) other pathogenic bacteria including Staphylococcus aureus and Salmonellae and (iv) yeast and mold. The result showed that 60.4 percent of total samples did not conform to the Notification Number 290 (B.E. 2548) of the Ministry of Public Health. Of these substandard samples, 39.1 percent contained coliform bacteria (MPN>2.2), 12.7 percent laced with E. coli, 8.1 and 1.0 percent with other pathogenic bacteria including Staphylococcus aureus and Salmonellae, and 46.7 percent with yeasts and molds, respectively. The samples were then divided based on Food and Drug Administration (FDA) registration. Results showed that 27.5 percent of 80 FDA-registered samples did not conform to Ministry of Public Health standards, while 82.9 percent of 117 non-registered samples were substandard. This indicated that most beverages packaged in sealed containers without FDA license did not conform to the standards, thus consumers should be aware of the unreliable quality and the safety of the beverages of choice.